Modeling And Stability Analysis Of Linear Actuated Finger - Abd Aziz, Ellyana Shaira; Kamarudin, Muhammad Nizam; Jali, Mohd Hafiz; Ghazali, Rozaimi (SERSC, 2017)
This paper presents the modeling and validation of a Linear Actuated Finger (LAF) with unknown behavior. In nature, LAF consists of servo, linkage, gear, inertia, stiffness, as well as nonlinearity such as mechanical backlash. The dynamic model is obtained via System Identification (SI) approach. The identification phase exploits the input-output data that represented by the voltage-angle relation of the LAF. By using Jury Stability criterion, the stability of the LAF can be shown without prior knowledge of pole-zero location in the s-plane. Then, simple discrete Proportional-Integral (PI) controller is formulated to validate the controllability as well as to observe the transient and steady-state behavior of the LAF model.